The Wall: Exploring inequality, waste and hope in Vrygrond and the adjacent Capricorn Business Park (Cape Town, SA) - Berning, Carey (Environmental Humanities, 2025)
The World Bank's 2022 report on inequality found South Africa (SA) to be the most unequal country in the world, reportedly ranking “first among 164 countries in the World Bank's global poverty database” (World Bank, The, 2022, p. 1). The primary reason for this inequality is inherited circumstances, which in SA, is closely tied to the unjust histories of colonialism and apartheid. In Muizenberg East, Cape Town, a still largely informal settlement, called Vrygrond, is located next to the highly securitized and so-called ‘eco-friendly' Capricorn Business Park. This small area in Cape Town exemplifies South Africa's inequality, with the Capricorn Business Park's high boundary wall acting as both a physical and metaphysical barrier between the business park itself and the adjacent Vrygrond community. As such, this study, in experimenting with a catalytic type of social science, examines the past and present spatial, social and economic divisions experienced in the space. The study aimed to conduct research that was generative and that facilitated the formation of relationships across the wall, in an effort to improve the environmental and social conditions of this area, further contributing to a resiliency against climate change. Using qualitative methods and participant observation, the study provides narrative accounts of life in Vrygrond, as mediated through a non-profit organisation (NPO) located in the community, called Where Rainbows Meet – including the NPO's efforts to address food security through their urban food garden. This NGO's development of their urban food garden cultivates food for the community of Vrygrond which continues to feel the unjust legacies of coloniality and apartheid. The study found that a proliferation of waste, on the Vrygrond side of the wall, while on the Capricorn side of the wall an eco-friendly business park enacts a vision of green capitalism as described by Sullivan (2009) and Scales (2017) ; it enacts the slow violence described by Nixon (2011) and the waste siege described by Stamatopoulou-Robbins (2020) in Palestine. The study demonstrates the difficulties of crossing the wall between the formal and informal economy in contemporary South Africa and poses questions about trickle down theories of economic development.